RF oscillator implementation using integrated CMOS surface acoustic wave resonators - Nordin, Anis Nurashikin; Zaghloul, Mona E. (Springer Netherlands, 2011)

(untitled)
This work is a proof of concept that a monolithic CMOS surface acoustic wave (SAW) resonator can function as an RF oscillator. The design of the oscillator includes the measurement characteristics of the CMOS SAW resonator, its matching networks, and RF amplifier is described. The integrated SAW resonator, with its operating frequency controlled by the spacing of its transducers was fabricated using a combination of CMOS plus post- CMOS processes. Based on the operation and performance of the SAW resonators, an equivalent circuit model of the CMOS SAW resonator was developed. A series resonant oscillator design was simulated using Microwave OfficeTM. The designed matching network improves both the insertion losses and the phase slope of the resonator, while the RF amplifier provides sufficient gain to ensure oscillation. Measurements conducted on the RF-CMOS SAW oscillator demonstrated oscillation at 600 MHz